Exploring English as an Additional Language Students’ Perceived Engagement in and Experience of Content Vocabulary Acquisition and Retention Through Immersive Virtual Reality Games - Sahinler Albayrak, Muleyke (Curtin University, 2022)
This thesis aimed to explore whether headset-mounted display virtual reality (HMD VR) games could serve as an innovative approach to enhance content vocabulary learning and foster subject content knowledge of Years 7 and 8 Middle Eastern students. Specifically, it aimed to measure these students’ content specific vocabulary acquisition and retention, examine their perceptions of and attitudes towards VR game-based learning, and offer best practices for educational institutions that support culturally and linguistically diverse (CALD) learners.